MANAJEMEN GURU PAI DALAM MENINGKATKAN PRESTASI SISWA MELALUI PEMBELAJARAN KOOPERATIF (Studi Kasus Pada SD Negeri Pasir Haur Kabupaten Bandung Barat) - Sukarelawan, Asep Ganjar (Institut Agama Islam Sahid (INAIS) Bogor, 2025)
The background of the problem research on elementary school Pasirhaur West Bandung is the lack of absorptive capacity of students in Islamic education, as evidenced by the results of the evaluation study were on average under the minimum completeness criteria (MCC). This fact illustrates that Islamic religious education (IRE) teacher as the person most responsible for organizing the learning process in the classroom has not managed optimally. Contributing factor less than the maximum use of time and learning strategy, then it needs to be implemented for the management of planning , organizing , implementation and evaluation of IRE teachers to improve student achievement . Through cooperative learning with two main components is the components of cooperative tasks and components of cooperative incentive structure. Cooperative tasks related to things that cause members to cooperate in completing the task group, whereas the incentive structure of cooperative is something motivating people to work together to achieve group goals. IRE teacher’s of planning management indicated by the functioning of the planning as outlined in the work program in the form of an annual program and the promissory note. Management organization which means IRE teachers in managing learning in the classroom, teacher management implementation shown by the efforts of teachers to use innovative teaching methods (cooperative learning). Management evaluation with conducting the assessment at the end of learning, midterm and final exams. Efforts made in the face of obstacles improving student achievement through discussion forums, discussions both schools under the leadership of the principal and in the forum Events Job Teacher IRE, and actively participate in competitions IRE from the district level to the district level. IRE 's goal-oriented management practices on improving student achievement and professionalism of teachers that have an impact on the quality of education.